Anti-N-methyl-D-aspartate receptor encephalitis: Case series of psychiatric presentations - Arpit Koolwal; Supriya Agrawal; Ghanshyam Das Koolwal; Kaveri Saxena; Ankit Daral (Annals of Indian Academy of Neurology, 2020)
Anti-NMDAR encephalitis is an autoimmune encephalitis with a typical clinical progression. Patients can often present to psychiatric outpatient departments (OPDs) mimicking psychiatric illnesses. In this case series, we have described two cases of adolescent age group that were eventually diagnosed with anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis. They had presented to psychiatry OPD and were admitted to the psychiatry ward. Both cases had predominantly, although varied, psychiatric symptoms with a variable course, response to treatment and prognosis. We have tried to speculate if initial presentation in anti-NMDAR encephalitis can be suggestive or can predict response to treatment and prognosis in a patient. We advocate a high degree of suspicion for psychiatrists toward patients presenting acutely in the first episode of mania or psychosis, particularly in adolescent age group.